The Green Box: An Electronically Versatile Perylene Diimide Macrocyclic Host for Fullerenes - Barendt, Timothy A.; Myers, William K.; Cornes, Stuart P.; Lebedeva, Maria A.; Porfyrakis, Kyriakos; Marques, Igor; Felix, Vitor; Beer, Paul D. (Journal of the American Chemical Society, 2020)
The powerful electron accepting ability of fullerenes akes them ubiquitous components in biomimetic donor-acceptor systems that model the intermolecular electron transfer processes of Nature's photosynthetic center. Exploiting perylene diimides (PDIs)The powerful electron accepting ability of fullerenes makes them ubiquitous components in biomimetic donor-acceptor systems that model the intermolecular electron transfer processes of Nature's photosynthetic center. Exploiting perylene diimides (PDIs) as components in cyclic host systems for the noncovalent recognition of fullerenes is unprecedented, in part because archetypal PDIs are also electron deficient, making dyad assembly formation electronically unfavorable. To address this, we report the strategic design and synthesis of a novel large, macrocyclic receptor composed of two covalently strapped electron-rich bis-pyrrolidine PDI panels, nicknamed the "Green Box" due to its color. Through the principle of electronic complementarity, the Green Box exhibits strong recognition of pristine fullerenes (C-60/70), with the noncovalent ground and excited state interactions that occur upon fullerene guest encapsulation characterized by a range of techniques including electronic absorption, fluorescence emission, NMR and time-resolved EPR spectroscopies, cyclic voltammetry, mass spectrometry, and DFT calculations. While relatively low polarity solvents result in partial charge transfer in the host donor-guest acceptor complex, increasing the polarity of the solvent medium facilitates rare, thermally allowed full electron transfer from the Green Box to fullerene in the ground state. The ensuing charge separated radical ion paired complex is spectroscopically characterized, with thermodynamic reversibility and kinetic stability also demonstrated. Importantly, the Green Box represents a seminal type of C-60/70 host where electron-rich PDI motifs are utilized as recognition motifs for fullerenes, facilitating novel intermolecular, solvent tunable ground state electronic communication with these guests. The ability to switch between extremes of the charge transfer energy continuum is without precedent in synthetic fullerene-based dyads.